2009
DOI: 10.1159/000242360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Industrial Processing on the Immunogenicity of Commonly Ingested Fish Species

Abstract: Background: Food-processing techniques may induce changes in fish protein immunogenicity. Allergens from >100 fish species have been identified, but little is known on the effects of processing on fish protein immunogenicity. Methods: IgE binding of sera of patients allergic to fresh and processed (smoked, salted/sugar-cured, canned, lye-treated and fermented) cod, haddock, salmon, trout, tuna, mackerel and herring and of hydrolysates based on salmon and whiting was investigated using immunoblot and inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 75 publications
3
43
0
Order By: Relevance
“…The raw extract contains 26 protein fractions, generally similar to the protein profile of raw yellowtail tuna [28,33], whereas the boiled extract has only 9 protein bands, probably due to denaturation of thermolabile proteins of 16-25 and 40-90 kDa. This protein pattern is also in accordance with other studies which reported thermolabile proteins between 20-100 [40] and 40-90 kDa [41] in multiple fish species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The raw extract contains 26 protein fractions, generally similar to the protein profile of raw yellowtail tuna [28,33], whereas the boiled extract has only 9 protein bands, probably due to denaturation of thermolabile proteins of 16-25 and 40-90 kDa. This protein pattern is also in accordance with other studies which reported thermolabile proteins between 20-100 [40] and 40-90 kDa [41] in multiple fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on tuna allergens have been conducted on several species of tuna such as Thunnus albacares/ yellowtail tuna [28,32,33], Thunnus alalunga/ albacore [16,32], Thunnus obesus /bigeye tuna [29,30] and Thunnus thynnus /bluefin tuna [31], while some other studies did not mentioned the tuna species [34]. To the best of our knowledge, there is only one short report on T. tonggol [35].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we included such treated food samples from pickled, canned and smoked fish and could quantify significantly lower parvalbumin levels. The solubility of parvalbumins in processed food may also be reduced by interaction with other matrix ingredients and formation of high-molecular-weight complexes [21]. In contrast, parvalbumin contents in extracts prepared from cooked fish fillets were only up to 25% lower than in raw fish.…”
Section: Discussionmentioning
confidence: 99%
“…The various treatments often, but not consistently, reduced IgE-binding, whereas some treatments and some sera also showed increased IgE-binding (Sletten et al, 2010).…”
Section: Heat and Other Food Treatmentsmentioning
confidence: 88%
“…The latter were shown to contain peptides with lower molecular weight than the former and to be less antigenic . Furthermore, chemically hydrolysed salmon had a reduced or abolished IgEbinding capacity (Sletten et al, 2010). The clinical significance of these findings has to be established.…”
Section: Chemical Hydrolysismentioning
confidence: 99%